5. Working group of SFPM: To implement motion management technologies for RT in clinical routine. (December 2017) - Ayadi, M.; Ailleres, N.; Bouilhol, G.; Bouscayrol, H.; Darréon, J.; Simon, L.
Abstract : Geometrical accuracy of radiotherapy (RT) of intra-thoracic organs (lung, liver, pancreas and breast) is limited by patient breathing. Indeed, breathing amplitude can vary from 1 to 2 cm (sometimes more) and should be taken in account for each step of the treatment process. For example, for Non-Small Cell Lung Cancer (NSCLC), this uncertainty tends to use large internal margins that can compromise tumor dose escalation, and thus satisfying local control, because of lung DVH limitation. This problem is especially critical for stereotactic treatment delivering up to 20 Gy per fraction to the target. This French working group proposes to update and complete the TG76 report (ref 2006) using the following outline for its report. First, the nature of the breathing motion and its consequences for RT is fully described. A detailed lexicon is also proposed. Indeed, several technical terms are used in the literature and sometimes the same word is used for very different techniques. Then the different treatment modalities dealing with the motion management are reported: simple safety margins around the target, motion limitation techniques (breath-hold, abdominal compression, high frequency ventilation), breathing synchronization of the beam (gating) and target tracking. An overview of the main commercial and technical/methodological tools and their clinical advantages should help users or future users to set up the treatment modality in clinical routine. This report also describes the associated imaging techniques for planning these treatments (principle, how to use them). In particular a section is dedicated to 4DCT. In addition the in-room imaging techniques is presented and criticized. At last, consequences of interplay effect that occurs when a modulated plan is delivered to a moving target, is discussed. The group is composed of French clinical medical physicists who have a concrete/practical experience in this domain. This group also brings knowledge and tips to implement these technologies in a clinical context.